Less is More: Perception as a fun way to Rich Minimalism. (March 2022) - Carbon, Claus-Christian; Utz, Sandra; Hesslinger, Vera M.
Perceptual science is important to understand how humans and other animals perceive and experience scenes, objects and events. So, it is the essential science to predict how we construct reality and our Umwelt. We learn from perceptual phenomena that we only need a minimal amount of information to create rich worlds of imagination and perception. As such, perception is the perfect analogue to what we would like to call "Rich Minimalism" – the way to save resources while having even more fun as our brains complete the missing parts in a creative way. Here, we briefly mention three little examples from basic research to demonstrate the power of perception for creating efficiency, effectiveness, and economy while having great fun with the resulting minimalism.